Analisis Motivasi Belajar Siswa Pada Mata Pelajaran Biologi di Sma Negeri 1 Luwuk - Anggo, Sulasmi; Nurlia, Nurlia; Marjuno, Siti Aisyah; Laita, Adeirma (Jurnal Biologi Babasal, 2023)
Motivation is a psychological state that comes from within a person to encourage feelings of pleasure and a strong will to carry out an action to achieve a goal. Student learning motivation is the encouragement that forms the basis for students to want to study well and earnestly both arising from within themselves and from outside. This study aims to determine students' motivation in biology subject at SMA Negeri 1 Luwuk. The type of research used is descriptive research with a qualitative approach. The research was conducted by distributing questionnaires to 215 respondents who were taken randomly from 562 populations. The results of this study indicate that 0.93% of students are classified as very low motivation, 14.90% of students are classified as low motivation, 61.40% of students are classified as high motivation and 22.80% of students are classified as very high motivation. So that in general students' learning motivation in biology subjects at SMA Negeri 1 Luwuk is in the very high category.